PENEGAKAN HUKUM LINGKUNGAN SEBAGAI UPAYA PEMBANGUNAN YANG BERKELANJUTAN - Zainudin Hasan; Maya Zulvi Astarida (Jurnal Ilmiah Advokasi, 2023)
The environment is a part that is tied to human life, the environment contains animal habitats and biodiversity in it, if the environment is damaged it will damage animal habitats and biodiversity around it so that in the end it will lead to the extinction of animals and biodiversity. Illegal logging results in direct or indirect changes to the physical properties and damage to sources of environmental biodiversity, resulting in environmental damage. The problem approach that will be used in this study is the normative juridical approach and the empirical approach. Law enforcement regarding environmental laws as an effort for sustainable development must be strictly implemented, especially in the case of illegal logging. The regulations governing this matter are with the promulgation of Law Number 41 of 1999 concerning Forestry which repeals the enactment of Law Number 5 of 1967. Then it was changed to Law Number 19 of 2004 concerning the Establishment of Government Regulations in Lieu of Law No.1 of 2004 concerning Amendments to Law Number 41 of 1999 concerning Forestry. In addition, the government has also enacted Law Number 18 of 2013 concerning Prevention and Eradication of Forest Damage. Law enforcement is very important, therefore it is hoped that law officials in reducing cases of illegal logging may be able to socialize about environmental damage if logging is illegal if it is carried out continuously to the community, or put up banners regarding prohibitions and sanctions obtained from illegal logging activities. As well as to the community is expected to be able to understand and understand the importance of the environment, let's protect the environment in order to achieve sustainable environmental development. Keywords: Environment, Logging, Law Enforcement.